Synthesis, Antibacterial Evaluation and Antifungal Study of New Biochemical Derivatives - Noor Sabah Muttaleb (Recent Trends in Infectious Diseases, 2026)
Bacterial and fungal infections have become widespread recently due to the spread of epidemics, diseases, and bacterial infections. As a result, infection rates have increased, prompting many researchers to develop new antibiotics to reduce the spread of these prevalent diseases. Researchers have prepared biochemical compounds similar in structure to drugs that eliminate infections and reduce their spread. One such derivative is imidazole; a well-known compound used in many medications for diarrhea and food poisoning. Imidazole and thiazole compounds are among the active compounds in the preparation of antibiotics, including sulfamethoxazole and other pharmaceutical preparations and antibacterial agents, due to their superior ability to penetrate bacterial cell walls. Therefore, the presence of an imidazole ring in any pharmaceutical drug is a catalyst for making the chemical compound an effective antibacterial agent against a wide range of bacterial infections. In this study, we took cyclic derivatives of chalcone, imidazole, and benzothiazole linked to the pyrrole ring, which was substituted with various groups in a series of newly prepared derivatives. These were characterized spectroscopically after preparation, and then bio-evaluation studies were conducted to measure their efficiency in the biological field, such as bacterial activity against types of bacteria. They also studied against fungi, and they gave good results indicating that they are efficient compounds in the biological field.
Keywords: Antibacterial; Antifungal; Infection; Medication; Resistance; antibiotics; biochemistry